Communication Strategy of the Deli Serdang Department of Culture, Youth, Sports and Tourism in Increasing Post-Covid-19 Tourist Visits - Muhammad Wahyu; Ahmad Tamrin Sikumbang (IHSA Institute, 2022)
The purpose of this study is to explain the strategy of Deli Serdang's Department of Culture, Youth, Sports, and Tourism in increasing tourist visits after Covid-19. The Covid-19 virus's presence in Indonesia has unintentionally hampered and limited activities and community activities. The impact is also felt in a variety of industries, including tourism. This study is a type of qualitative research that employs a descriptive approach method. The data for this study was derived from interviews with the Director of Tourism and Creative Economy. The findings revealed that the strategy used by the Deli Serdang Department of Culture, Youth, Sports, and Tourism in increasing tourist visits after Covid-19 was to promote and create content on social media accounts such as Instagram, Tiktok, Facebook, Twitter, and Youtube, as well as utilizing radio electronic media that includes tourist destinations in Deli Serdang Regency, and provides a small note that the public or visitors still adhere to the health protocols that have been established.